Hilar cholangiocarcinoma patients accepting preoperative percutaneous transhepatic biliary drainage experienced high incidence of portal vein invasion and lymph node metastasis - Cai, Yingke; Yao, Yuxuan; Dong, Yi; Wang, Dang; Luo, Jing; Heng, Gang (Frontiers in Oncology, 2025)
BackgroundPercutaneous transhepatic biliary drainage (PTBD) was widely used for bile drainage in hilar cholangiocarcinoma (HCCA) patients, due to its exact effectiveness in relieving obstructive jaundice. However, the potential association between PTBD and increased local tumor spread (including portal vein invasion and lymph node metastasis) remained unclear, as this procedure might prolong the waiting time and lead to potential risks of portal vein injury. This study aimed to investigate whether HCCA patients undergoing PTBD exhibit higher risks of portal vein invasion and lymph node metastasis after radical resection.MethodsThe clinical data of 341 HCCA patients was retrospectively analyzed. PTBD was exclusively used as the preoperative biliary drainage method, excluding patients who underwent endoscopic nasobiliary drainage or endoscopic biliary stenting. Portal vein invasion and lymph node metastasis were verified by postoperative pathological examinations.ResultsIn this study, 163 patients (47.8%) received preoperative PTBD. These patients experienced significantly higher risks of portal vein invasion [odds ratio (OR): 1.86, p = 0.027] and lymph node metastasis (OR: 1.94, p = 0.008) compared to those 178 patients (52.2%) in the non-PTBD group. The Kaplan–Meier survival analysis revealed significantly better OS (p = 0.039) in the non-PTBD group. Causal mediation analysis revealed that the effect of PTBD on survival was partly mediated by portal vein invasion and lymph node metastasis. Additionally, the length of hospitalization in PTBD group was obviously longer (26.7 days vs. 21.8 days, p = 0.002).ConclusionPreoperative PTBD was associated with increased incidence of portal vein invasion and lymph node metastasis in HCCA patients accepting R0 resection.